FRI0374 Inflammatory Exosomes Implicate a Role for Epstein Barr Virus Infection in the Pathophysiology of Systemic Lupus Erythematosus. (9th June 2015) - Pegtel, D.M.; Masoumi, N.; Tsang-A-Sjoe, M.W.; van Eijndhoven, M.A.; Bultink, I.E.; Heutinck, K.M.; Grünberg, K.; ten Berge, R.J.; Gelderman, K.A.; von Blomberg, B.M.; Middeldorp, J.M.; Voskuyl, A.E.
Abstract : Background: The pathogenesis of Systemic Lupus Erythematosus (SLE) is incompletely understood. Low concordance rates in monozygotic twins and geographical differences in disease risk, suggest involvement of environmental factors in the etiology of SLE. Virtually all patients with SLE have increased antibody titers against EBV antigens, chronically amplified infection frequencies, and 99-100% of young SLE patients seroconvert against Epstein-Barr virus, compared to only 70% of controls. However, a specified role for EBV in SLE pathogenesis remains unclear. Recently, we discovered that EBV-infected B cells secrete highly inflammatory viral RNAs (EBERs) via extracellular vesicles (EVs). Objectives: We aimed to investigate the extent of anti-EBV AB responses in SLE patients and study the potential pro-inflammatory role of EBV-secreted, EBER1-laden extracellular vesicles and assess EBV-RNAs as biomarkers in SLE tissues. Methods: We explored the molecular basis of altered anti-EBV antibody responses at the epitope level, by immunoblot and peptide-based ELISA in serial samples of SLE patients. We determined EBERs with RT-PCR and in situ hybridization in blood, urine and affected tissue (renal, skin) of SLE patients (with or without nephritis). The inflammatory properties of EBV-EVs were studied in vitro using primary cultures. Results: We demonstrate that aberrant antibodies against EBV-antigens and presence of extracellular EBV small RNA (EBER1) distinguish SLE patient sera from rheumatoid arthritis patients and healthy individuals. SLE patients with renal involvement have a distinct pattern of anti-EBV antibody reactivity and lack detectable EBER1 in circulating plasma exosomes. However, surprisingly high levels of EBER1 were detected in lupus nephritis (LN) biopsy material, but not in IgA nephritis tissue. This is compatible with an exogenous (blood-born) source of EBER1, because EBV DNA was near absent and similar observations were made in SLE-associated skin lesions. In situ hybridization showed EBER1 positivity in tubular epithelial cells (TECs). Purified EVs from latent EBV-infected cells are internalized by both primary TEC and plasmacytoid dendritic cells in a phosphatidylserine receptor-dependent manner, causing pro-inflammatory IL-6 production upon EBER1 recognition by viral sensors. Conclusions: EBV-infection is deregulated in SLE patients based on anti-EBV Ab responses and elevated levels of extracellular EBER1 in circulation that targets the renal epithelium and skin. Our findings in vitro confirm strong pro-inflammatory functions of EBER1-containing exosomes that target specific cell types, shedding new light on EBV as co-factor in the pathophysiology of SLE and the role of EVs in autoimmune disease. Disclosure of Interest: None declared